2016
DOI: 10.1186/s13046-016-0452-6
|View full text |Cite
|
Sign up to set email alerts
|

miR-589-5p inhibits MAP3K8 and suppresses CD90+ cancer stem cells in hepatocellular carcinoma

Abstract: BackgroundCancer stem cells (CSCs) are important in the tumorigenesis and progression of hepatocellular carcinoma (HCC). MicroRNAs (miRNAs) play crucial roles regulating CD133+ and EpCAM+ CSCs in HCC, although it is unclear whether miRNAs regulate CD90+ CSCs in HCC.MethodsThe miRNA profiles of CD90+ and CD90- HCC cells were analyzed using a miRNA microarray and quantitative real-time PCR (qRT-PCR). CSC characteristics were examined by qRT-PCR and Western blot of pluripotency-associated genes, clone and sphere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…Li et al reported that miR-589 was significantly downregulated in cisplatin-resistant A549, and transfection with miR-589 resulted in an increased sensitivity to cisplatin (10). A later study showed that miR-589-5p could downregulate the stemness characteristics of CD90 + cancer stem cells (CSCs) of HCC in part by silencing MAP3K8 (11). Our findings revealed that the loss of miR-589-5p by hypermethylation accelerated NSCLC development through increasing the expression of HDAC5.…”
Section: Hypermethylation Of Mirna-589 Promoter Leads To Upregulationmentioning
confidence: 58%
“…Li et al reported that miR-589 was significantly downregulated in cisplatin-resistant A549, and transfection with miR-589 resulted in an increased sensitivity to cisplatin (10). A later study showed that miR-589-5p could downregulate the stemness characteristics of CD90 + cancer stem cells (CSCs) of HCC in part by silencing MAP3K8 (11). Our findings revealed that the loss of miR-589-5p by hypermethylation accelerated NSCLC development through increasing the expression of HDAC5.…”
Section: Hypermethylation Of Mirna-589 Promoter Leads To Upregulationmentioning
confidence: 58%
“…CD90 may be involved in HCC only under certain conditions. Although CD90 is a typical marker of CSCs in HCC and high CD90 expression has been linked to higher recurrence rate 38,39 , one study reported that CD90+ CSCs-like cells in the liver may participate only in late-stage liver cancer associated with hepatitis B virus infection 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, miR-1, miR-21, miR-122, miR-221, miR-29, miR-500 and many other microRNA are reported to be aberrantly expressed in HCC and can act as biomarkers [16][17][18][19][20][21]. Although MiR-589-5p is a poorly studied microRNA in cancer, there is the following research; (1) Zhang et al demonstrated that it inhibits MAP3K8 and suppresses CD90+ cancer stem cells in HCC [22]; (2) Long et al found that it promotes the cancer stem cell characteristics and chemo-resistance of HCC cells by targeting multiple negative regulators of the STAT3 signaling pathway [23] and (3) Huang et al reported that the expression of miR-589-5p is down-regulated in radiated laryngeal squamous carcinoma stem cells [24]. However, more biological effects of miR-589-5p need to be revealed.…”
Section: Discussionmentioning
confidence: 99%